Managing Success in Viet Nam: Macroeconomic Consequences of Large Capital Inflows with Limited Policy Tools - Jayant Menon (Asian Development Bank (ADB), 2009)
Viet Nam has experienced spectacular economic growth over the past decade, in part the result of massive foreign direct investment (FDI) inflows. Although much has been written on the impacts of FDI in developing countries, previous studies have generally ignored macroeconomic consequences in cost-benefit assessments. These macroeconomic aspects can be particularly important in transitional economies like Viet Nam, where some of the tools for macroeconomic stabilization may be blunt or unavailable. First, capital inflow growth needs to be accommodated by real exchange rate appreciation. In dollarized economies like Viet Nam, the nominal exchange rate cannot be relied upon to deliver it, so inflation usually results. In these economies, it is also difficult for the central bank to conduct open market operations to sterilize large capital inflows or mop up excess liquidity. Again, this could feed inflation. The combination of a young and inexperienced banking system and an investment-hungry state-owned enterprises (SOE) sector only exacerbates the situation, and increases the risk of imbalances that could result in crisis.
hdl:11540/1801
Keywords: F21; F32; F49; 330; capital inflow; macroeconomic adjustment; FDI; real exchange rate; Viet Nam